AB1025 The superb microvascular imaging is more sensitive than conventional power doppler imaging in detection of active synovitis in rheumatoid arthritis patients. (15th June 2017) - Lee, GY; Kim, S; Choi, ST; Song, J-S
Abstract : Background: Precise evaluation of synovial inflammation and bony deformity is very important for the management of rheumatoid arthritis (RA). One of the most popular used methods to detect synovial inflammation and bony erosion is ultrasonography. Previous literatures revealed that US using power Doppler imaging (PDI) could detect more sensitive synovial inflammation than conventional radiography. However, there are still some limitations in ultrasonography. The superb microvascular imaging (SMI) is a new software technology introduced by Toshiba, which can detect a vascularity more sensitively without artifacts. Objectives: In this prospective study, we evaluated the clinical usefulness of the SMI compared to PDI for the detection of active synovitis in patients with RA. Methods: This prospective observational study includes 56 patients with RA (42 females; mean age, ), from June 2015 to October 2016. The mean age of RA patients was 53.2±17.6 years, and 42 patients were female (75.0%). All the included patients underwent ultrasound about both wrists and hands (total 22 joints; wrist joints, metacarpophalangeal joints, and proximal interphalangeal joints). All the ultrasound examinations were performed at the volar side of the wrists and hands using both conventional PDI and SMI which use Aplio TM 500 Ultrasound (Toshiba Medical Systems Corporation). Their results were scored for each joint from grade 0 to grade 3 according to the vascularity (grade 0, no vascularity; grade 1, single vessel; grade 2, vascular flow less than 50% in field of view; grade 3, equal to 50% or more). The sum of grades for 22 joints was compared between PDI (PDI-sum) and SMI (SMI-sum). The correlation between the sum of grades values and inflammatory laboratory parameters including the erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and disease activity score 28 (DAS28) were also evaluated. Results: The mean values of ESR, CRP and DAS28 were 27.13±18.06 mm/hr, 6.78±9.14 mg/L, and 2.71±1.11 respectively. The positive rates of rheumatoid factor and anti-cyclic citrullinated antibody were 73.2% and 75.0%, respectively. The sum of grades for 22 joints was significantly higher in SMI-sum compared to PDI-sum (10.27±6.20 vs. 5.80±3.79, p <0.001). The SMI-sum was highly correlated with the PDI-sum score (γ=0.800, p <0.001). The SMI-sum showed positive correlation with DAS28, tender joint count, swollen joint count, visual analogue pain scale, and CRP level (γ=0.486, p <0.001; γ=0.385, p =0.003; γ=0.467, p <0.001; γ=0.547, p <0.001; γ=0.351, p =0.008, respectively). The number of clinical remission (DAS28 score below 2.6) was 28 (50.0%). The SMI-sum was significantly higher than PDI-sum in patients with clinical remission (7.96±5.39 vs. 4.64±3.03, p <0.001). All of the patients with clinical remission showed active synovitis at more than one joint in SMI. Conclusions: SMI showed a more sensitive vascularity in RA patients than PDI. We could detect active synovitis through SMI in the RA patients with clinical remission. SMI could be a useful technology for the evaluation of synovitis in RA patients, especially for the detection of clinically subtle, but active synovitis in RA patients with remission. Disclosure of Interest: None declared